Let's evaluate the quadratic equation \((2x−7)(x+9) = 0\) by substituting the given values into the equation and checking whether or not they satisfy the equation.
Evaluating Given Values
For Value 0:
- Substitute: \(x = 0\) \[ (2(0)−7)(0+9) = (−7)(9) = -63 \]
- Evaluate:
- The equation equals \(-63\), which does not equal \(0\).
- True or False Statement: \(-63 = 0\) False
For Value 3:
- Substitute: \(x = 3\) \[ (2(3)−7)(3+9) = (6−7)(12) = (−1)(12) = -12 \]
- Evaluate:
- The equation equals \(-12\), which does not equal \(0\).
- True or False Statement: \(-12 = 0\) False
For Value -9:
- Substitute: \(x = -9\) \[ (2(-9)−7)(-9+9) = (−18−7)(0) = (−25)(0) = 0 \]
- Evaluate:
- The equation equals \(0\), which does equal \(0\).
- True or False Statement: \(0 = 0\) True
For Value 9:
- Substitute: \(x = 9\) \[ (2(9)−7)(9+9) = (18−7)(18) = (11)(18) = 198 \]
- Evaluate:
- The equation equals \(198\), which does not equal \(0\).
- True or False Statement: \(198 = 0\) False
Summary of Results
| Value | Substituted | Evaluate: Step 1 | Step 2: True or False Statement | |-------|---------------------------|------------------------------|----------------------------------| | 0 | \((2(0)−7)(0+9)\) | \((−7)(9) = -63\) | \(-63 = 0\) False | | 3 | \((2(3)−7)(3+9)\) | \((−1)(12) = -12\) | \(-12 = 0\) False | | -9 | \((2(-9)−7)(-9+9)\) | \((−25)(0) = 0\) | \(0 = 0\) True | | 9 | \((2(9)−7)(9+9)\) | \((11)(18) = 198\) | \(198 = 0\) False |
Feel free to check your answers as you work and make any necessary adjustments!